Deriving Aggregate Results with Incremental Data using Materialized Queries - Chakraborty, Sonali; Doshi, Jyotika (International Journal of Computer Sciences and Engineering, 2025)
OLAP queries perform analytical processing on enterprise warehouse data. These queries are implemented using aggregate as well as non-aggregate functions. Result extraction using OLAP queries involves traversal through huge number of warehouse records. For repeated queries, processing time can be saved by storing queries along with its result and other parameters like timestamp, frequency, threshold in relational database MQDB. With periodic data warehouse refresh, incremental results for the frequent queries are processed using data marts and results are combined with existing results. This paper depicts the methodology to derive results based on different aggregate functions giving the effect of incremental data. Some aggregate functions may require other measures to be stored for compiling results.